Identifying Factors Encouraging University Students to Play Computer Games - Recep ÖZ,; Murat Tolga KAYALAR,; Ayhan KOÇ, (PJDOL, 2023)
The study employed a quantitative research design using the general survey model to understand a large research population without intervening in variables. It involved 552 teacher candidates from an education faculty in Eastern Anatolia, Turkey, with 142 males and 410 females participating voluntarily. Data were collected using the Computer Game Motivation Scale (CGMS) with 17 items and five sub-dimensions (Concentration, Enjoyment, Escape, Learning, and Socialization), assessed on a five-point Likert scale (1 = Strongly Disagree, 5 = Strongly Agree). The reliability coefficients (Cronbach's Alpha) ranged from .77 to .95 for scale structures and were .94 for the entire scale. Internal consistency coefficients for sub-dimensions varied from .78 to .94, with .93 for the overall scale. The information form included gender, department/unit, perceived income status, and place of residence inquiries. Male students had higher gaming addiction scores than females, and those in verbal programs scored higher than numerical programs. 2nd and 3rd-year students had higher gaming addiction scores, and students with a perception of very poor income also scored higher in gaming addiction. Interestingly, the place of residence did not significantly affect gaming addiction, likely due to widespread internet and technology access. In summary, this study highlighted how gender, program, class level, and income perception impact gaming addiction among university students, while place of residence does not seem to play a significant role.